Capital at the core: Spatial inequalities in Polish corporate bonds - Węgrzyn, Paweł; Kruszka, Michał (Bulletin of Geography. Socio-economic Series, 2026)
This paper aims to determine whether the regional distribution of corporate bond issuance in Poland is driven by spatial interdependence or by local economic fundamentals. Using a comprehensive dataset of outstanding corporate bonds for year-end 2024 across 73 NUTS-3 regions, the study employs Moran’s I statistics and regression models including Ordinary Least Squares (OLS) and Spatial Lag of X (SLX). Results reveal an extreme issuance concentration in the Warsaw region, accounting for 62% of the total. However, no significant spatial autocorrelation was detected, with neither Moran’s I nor the SLX specification yielding significant evidence of spatial dependence. The strongest determinants of issuance activity were regional wealth (GDP per capita) and innovation capacity (number of filed inventions). By contrast, population density, the number of registered firms, and distance from Warsaw were statistically insignificant. ...